Are there any gender differences in students' emotional reactions to programming learning activities? - Coto, Mayela (2019)
Novice programmers experience a wide set of emotions when they are learning to program. This exploratory study analyzes the emotions experienced by a group of students when solving diverse programming tasks. The goal was to understand if there are gender differences in the emotions reported by the students. A self-report tool to track emotions was used. The results show that, regardless of the type of learning activity, there is a tendency for women to attribute themselves negative emotions to a greater extent, which happens to be the opposite with men. It is concluded that further research is needed to understand the factors that cause these differences.